Effects of game-based conditioning training on volleyball skill accuracy in junior players - Kristicevic, T.; Madic, D.; Krakan, I. (Acta Kinesiologica, 2016)
In recent years, an approach called game-based training has been developed. The aim of our research is to determine the effects of game-based training on accuracy in adolescent volleyball players. Forty two adolescent volleyball players (16,26±1,01 years) participated in this study. Players were randomly allocated into a small-sided games group (n = 22) and a control group (n = 20). Each player participated in a 8-week training program that included 3 organized court training sessions per week. Participants were tested for passing, setting, serving and serving under fatigue accuracy. Both groups made significant increases in serving accuracy (p < 0.05) after 8 weeks of training. However, significant interaction effect between the groups was not found for all variables. Control group was involved in traditional instructional training induced significant improvements in forearm passing, setting and serving accuracy. To conclude, game-based training appears to have similar effects with instructional training in improving skill accuracy in junior volleyball players.